Exploring the Direct and Mediated Impacts of User Perceptions on Intention to Use E-Wallets - Razan Dzaky Musyaffa; Fredianaika Istanti (Universitas Bina Sarana Informatika, 2026)
The​‍​‌‍​‍‌ rapid growth of e-wallets in Indonesia has been great especially in Semarang where a lot of people have adopted this payment method however users have also experienced problems in the understanding of the application features, easy operation, and concerns over data security. This study looked at the direct and indirect effects of perceived usefulness, perceived ease of use, and perceived security on the intention of using e-wallets in Semarang, with attitude as the mediating variable. A quantitative cross-sectional survey was conducted among 165 respondents using a five-point Likert scale. The data were analyzed using the PLS-SEM method. The findings indicate that perceived usefulness and perceived ease of use substantially impact one's attitude; however, perceived security has no effect; perceived usefulness and attitude considerably influence the intention to use, yet perceived ease of use and perceived security do not; and finally, the interaction between attitude and perceived usefulness as well as perceived ease of use significantly predicts intention to use whereas the interaction between attitude and perceived security is not significant. The results demonstrate that e-wallet adoption intention in Semarang is mostly influenced by users' perception of the usefulness and ease of the system which calls for service providers to focus more on functional value and user ​‍​‌‍​‍‌experience.